ID: 123. Issue 4 (April 2016) - Sysol, JR; Chen, J; Singla, S; Natarajan, V; Machado, RF; Comhar, S; Erzurum, SC
Abstract : Rationale: Pulmonary arterial hypertension (PAH) is a severe, progressive disease characterized by increased pulmonary arterial pressure and resistance due in part to uncontrolled vascular remodeling. The mechanisms contributing to vascular remodeling in PAH are poorly understood and involve rampant pulmonary artery smooth muscle cell (PASMC) proliferation. We recently demonstrated the important role of sphingosine kinase 1 (SphK1), a lipid kinase producing pro-proliferative sphingosine-1-phosphate (S1P), in the development of pulmonary vascular remodeling in PAH. However, the regulatory processes involved in upregulation of SphK1 in this disease are unknown. Objective: In this study, we aimed to identify novel molecular mechanisms governing the regulation of SphK1 expression, with a focus on microRNA (miR). Using both in vitro studies in pulmonary artery smooth muscle cells (PASMCs) and an in vivo mouse model of experimental hypoxia-mediated pulmonary hypertension (HPH), we explored the role of miR in controlling SphK1 expression in the development of pulmonary vascular remodeling. Methods and Results: In silico analysis identified hsa-miR-1-3p (miR-1) as a candidate targeting SphK1. We demonstrate miR-1 is down-regulated by hypoxia in human PASMCs and in lung tissues of mice with HPH, coinciding with upregulation of SphK1 expression. PASMCs isolated from patients with PAH had significantly reduced expression of miR-1. Transfection of human PASMCs with miR-1 mimics significantly attenuated activity of a SphK1-3'-UTR luciferase reporter construct and SphK1 protein expression. miR-1 overexpression in human PASMCs also inhibited proliferation and migration under normoxic and hypoxic conditions, both important in pathogenic vascular remodeling in PAH. Finally, we demonstrated that intravenous administration of miR-1 mimics prevents the development of experimental HPH in mice and attenuates induction of SphK1 in PASMCs. Conclusion: These data demonstrate that miR-1 expression in reduced in PASMCs from PAH patients, is modulated by hypoxia, and regulates the expression of SphK1. Key phenotypic aspects of vascular remodeling are influenced by miR-1 and its overexpression can prevent the development of HPH in mice. These studies further our understanding of the mechanisms underlying pathogenic pulmonary vascular remodeling in PAH and could lead to novel therapeutic targets. Supported by grants NIH/NHLBI R01 HL127342 and R01 HL111656 to RFM, NIH/NHLBI P01 HL98050 and R01 HL127342 to VN, American Heart Association Predoctoral Fellowship (15PRE2190004) to JRS, and NIH/NLHBI NRSA F30 Fellowship (FHL128034A) to JRS.